Spatio-temporal evaluation of ionospheric disturbances before, during and after earthquakes using differential rate of TEC (DROT) from GPS measurements - Karatay, Secil; Arikan, Feza; Pirti, Atinc (SPRINGER, 2025)
This study presents a comprehensive spatio-temporal analysis of ionospheric disturbances associated with seismic activity by applying the Differential Rate Of TEC (DROT) algorithm to GPS-based Total Electron Content (TEC) data. The investigation covers ten major earthquakes (Mw 9.0-5.6), examining ionospheric variability across pre-seismic, co-seismic, and post-seismic periods, alongside geomagnetically quiet and disturbed days. Results reveal that ionospheric perturbations are not confined to the pre-earthquake phase; significant anomalies are also observed during and up to six days after the seismic events. On earthquake days, DROT values predominantly cluster between 60 and 70%, indicating large-scale disturbances, while medium-scale disturbances (50-60%) are prevalent in the days leading up to and following the earthquakes. Spatial analysis shows stronger disturbances within 500 km of epicenters, diminishing with distance. The findings support the Lithosphere-Atmosphere-Ionosphere Coupling (LAIC) model, highlighting the sustained influence of seismic processes on the ionosphere. By distinguishing between seismically and geomagnetically induced disturbances, this study underscores the potential of DROT as a tool for real-time ionospheric monitoring and contributes to efforts in earthquake precursor detection and early warning systems.
Keywords: Ionospheric disturbances; Earthquake precursors; Total Electron content (TEC); Differential rate of TEC (DROT); Spatio-Temporal analysis; AIR WAVES; ATMOSPHERE; ANOMALIES; GROUNDWATER; EMISSIONS; TAIWAN; Environmental Sciences & Ecology; Geology; Water Resources